Heart to spine measurements to detect left atrial enlargement in dogs with mitral insufficiency - Sánchez Salguero, Xavier (Ir Vet J, 2019)
BACKGROUND: Radiography is useful to determine left atrial (LA) size when echocardiography is not available. Recently, the authors have described Radiographic Left Atrial Dimension (RLAD) as a new radiographic measurement to assess LA size. The objective of this study was to assess the clinical usefulness of 2 new radiographic measurements to detect and quantify left atrial enlargement (LAE) compared to RLAD and using left atrium to aortic root (LA/Ao) ratio as gold standard. These new measurements, bronchus-to-spine (Br-Spine) and RLAD-to-spine (RLAD-Spine) may be more precise in cases were LA boundaries are not well defined. Fifty dogs, 25 with and 25 without LAE were recruited. Reference LA/Ao ratio was assessed by 2D echocardiography and LAE was considered if LA/Ao > 1.6. Br-spine was measured as a straight vertical line from the main stem bronchus to the ventral border of the vertebra situated immediately dorsal to the heart base. RLAD-Spine was measured from RLAD endpoint perpendicularly to spine. The correlation of RLAD, Br-Spine and RLAD-Spine methods with LA/Ao and their sensitivity and specificity for detecting LAE were calculated. Receiver Operating Characteristic (ROC) curves were used to estimate the optimal cut-off for each method. RESULTS: Correlations between Br-Spine, RLAD-Spine, RLAD and LA/Ao ratio were − 0.66, − 0.76 and 0.89 respectively (P < 0.001). Sensitivity at the optimal cut-off values for detecting LAE were 32.0, 64.0 and 96.0%, respectively. Specificity was 96.0% in all cases. CONCLUSION: Br-Spine and RLAD-Spine were less sensitive radiographic measurements than RLAD in detecting LAE in dogs. Both Br-Spine and RLAD-Spine may not be good alternatives to RLAD.